Representações de estudantes sobre o abuso e assédio sexual na educação física - Machado, Carolina Pereira (2024)
Sexual harassment remains a prevalent issue in our society, affecting many countries around the world, with women being the primary victims. This phenomenon manifests in various settings such as public transportation, schools, higher education courses, workplaces, and sports, with a significant occurrence in the field of Physical Education. This investigation aimed to characterize the presence of sexual abuse in school physical education and sexual harassment in professional training in the field. The importance of this research lies in the need to deepen the understanding of the incidence of sexual harassment in the field of Physical Education, as the number of studies in this area is limited in Brazil. Additionally, the data obtained make the problem of sexual harassment in this environment concrete and scientifically evident, encouraging the search for solutions to this issue. The research is characterized as mixedmethod in nature and exploratory-descriptive in its objectives. After approval by the ethics committee and signing of the Informed Consent Form (ICF), 212 students from the Physical Education undergraduate and graduate courses at a public university in Rio Grande do Sul participated in the first stage of the research by answering a questionnaire. In the second stage, 9 female students agreed to participate in individual interviews, which were recorded on a digital device. The questionnaire data were analyzed using descriptive statistics, while the information collected in the interviews was analyzed using thematic analysis with the assistance of NVIVO 12 software. The study results reveal the alarming prevalence of abuse and sexual harassment in school physical education and professional training in Physical Education. Among the 212 students, 19.8% reported being victims and 42.5% witnessed abuses in school physical education, while 16% experienced and 28.8% witnessed harassment during their studies. The sports court, classroom environment, school yard, and bathrooms and/or changing rooms were identified as the main locations where these incidents occurred, indicating that there is no specific place for the phenomenon to happen, and it can occur anywhere. From the information obtained in our research, we found that the most common forms of sexual harassment are suggestive looks or gestures, sexually explicit comments, unwanted touching, and sexually charged jokes, as reported by both victims and those who witnessed these incidents in the academic environment. The research highlights the inadequacy of institutional responses and the urgent need for education about consent and respect, as well as the creation of safe environments and effective reporting policies. Sexual harassment negatively impacts mental health, academic performance, and women's participation in physical activities, underscoring the need for educational and preventive measures to combat the issue and support victims.